Storying and Re-storying Indigenous Content, Perspectives, and Histories in an Elementary Arts Based Curricular Experience - Ragoonaden, Karen; Macintyre Latta, Margaret; Hanson, Kelly; Draper, Rhonda; Coble, Jordan (Alberta Journal of Educational Research, 2020)
As part of a larger study focusing on the interdependence of creative and critical curricula, this research examines how an arts experience in an elementary school was re-storied, with the guidance of local and place-based First Nation community members, as an exploration of decolonizing curriculum. A school-based musical theatre experience titled Re-Storying Canadian History, which intended to address concerns about Canada’s 150th anniversary, served as a critical and creative medium for increasing awareness of the existing plurality of First Nation identities, cultures, and languages. Framed as a case study, the experiential narratives of elementary school students and their educators provided a space, a time, and a place to initiate and to discuss decolonization processes in elementary school curricula. Three interpretive devices, storying and re-storying, broadening, and burrowing engaged educators and their students in reconnecting teaching and learning with Indigenous content, perspectives, and histories. Key words: Storying and Re-Storying, Decolonization, Arts Based Research, Creative and Critical Curriculum, Truth and Reconciliation Commission S'insérant dans le cadre d’une plus grande étude portant sur l’interdépendance de la criticalité et de la créativité des programmes d’études, cette recherche examine la réitération d’une expérience artistique dans une école élémentaire sous la direction de membres de la communauté locale des Premières Nations comme une étude de la décolonisation du curriculum. L’école a présenté une production de théâtre musical intitulée Re-Storying Canadian History (Reprise de l’histoire du Canada) dont le but était d’aborder des préoccupations quant au 150e anniversaire du Canada. La présentation a servi d’instrument critique et créatif pour mieux faire prendre conscience de la pluralité des identités, des cultures et des langues des Premières nations. Présentés comme une étude de cas, les récits expérientiels des élèves de l’élémentaire et leurs enseignants offraient un espace, un moment et un lieu à l’initiation et à la discussion de processus de décolonisation dans les programmes d’études de l’élémentaire. Trois outils interprétatifs — la narration et la narration par réitération, l’élargissement et l’enfouissement — ont guidé les élèves et leurs enseignants alors qu’ils retissaient les liens entre l’enseignement et l’apprentissage et les récits, le contenu et les perspectives autochtones. Mots clés : narration et narration par itération, décolonisation, recherche basée sur les arts, curriculum créatif et curriculum de base, Commission de vérité et réconciliation